- Convert x+9=4(x-1)^2 to standard form?

x + 9 = 4(x-1)^2
x + 9 = 4(x^2 - 2x + 1)
x + 9 = 4x^2 - 8x +4
0 = 4x^2 -9x - 5

Read more

Read more

Read more

Read more

Show more results

Discover Questions

Help me and tell me which topic this comes from? Given that sin 40° = a, express the following in terms of a. (i) tan 40° (ii) cos 40°? IfA customer gives you a $100 bill for a purchase that totals $22.75. What is the best money combination to gi? Solve for y:
Log10 (-2y²) - Log10 (4y) = x
Evaluate y when x - -1.3? What is 10^-8.33? Decide whether the sentence is true or false. Antes = before; Después = after La tercera está después de la segunda.?

Answer #1| 06/02 2014 20:3495 %